Planning for Veterans' Success! The Degree Map as an Advising Solution - Tracey M Richardson (Online Learning, 2014)
Due of the expected influx of veterans attending college, it is critical that higher education not only be cognizant of the projected growth, but take a proactive stand and properly plan for these students’ success. Academic planning begins with the advising professionals developing open communications and be able to guide veteran students through the matriculation process. The purpose of this mixed method study is to explore the potential impact of degree maps on facilitating veteran students’ success. This study’s findings suggest the degree map is a powerful tool to help students through class selection and sequencing. The results provide insight into the similarities and differences between military, veteran, and civilian adult students’ needs. The degree map data provides transparency that will contribute to institutional and governmental monitoring for ongoing outreach to student veterans.